Realization of memristor and synaptic simulation behaviors based on LiNbOx. Issue 6 (15th March 2023) - Bamao, Anhe; Xia, Yaxin; Ma, Guokun; Yuan, Xiaoxu; Yang, Zisheng; Chen, Ao; Lin, Chun-Chu; Chang, Ting-Chang; Wang, Hao
Abstract: Devices suitable for neuromorphic computing were urgently needed. Here, by doping lithium metal atoms in solid electrolyte NbOx, a new nonvolatile memory device Pt/LiNbOx /TiN was fabricated and demonstrated typical bipolar resistive storage characteristics. Besides, continuous conductance states were obtained in both DC and pulsed modes and the paired-pulse facilitation (PPF) and spike-timing-dependent plasticity learning (STDP) behavior were successfully simulated by using appropriate pulse sequences, which were derived from the combined action of lithium and oxygen ions. Furthermore, the convolutional neural network（CNN）based on the LiNbOx memristor achieved high accuracy in MNIST dataset, indicating the great potential of the device for applying in neuromorphic computations.